Social Support and its relationship to Psychological Hardiness among Adolescent Girls affected by the Corona Pandemic (COVID-19) in Medina - Al-Kehaili, Fatima Atyah; Al-Ahmadi, Maria Taleb (Journal of Educational and Psychological Sciences, 2022)
This study aimed at recognizing the level of social support and psychological Hardiness of a sample of adolescent girls affected by the Corona (COVID-19) in Madinah, and the correlation between them was revealed, and the relational descriptive approach was used, where a measure of social support and psychological hardiness was applied from Sayed's study (2012), with the researcher's modification to fit the study sample. The research community consisted of (1285) female students, and their age range ranged from (13-19 years old). A sample was chosen consisting of (457) adolescent students affected by the Coronavirus (COVID-19) pandemic, and the study reached the following results:-The social support scores in the study sample were of a grade level (high), and the average value of the scores was higher, the sum of the degrees of rise in height (high). The general arithmetic mean value, total share size (4.15), And the presence of a statistically significant positive moderate correlation relationship between degrees of psychological Hardiness and their degrees of appreciation for social support at the level of significance (0.01 ≥α)-  The higher the level of appreciation for social support, the higher the level of psychological Hardiness.The results also found that there are statistically significant differences between the averages of the total score for the scale of social support in the study sample due to the school stage variable in favor of middle school students, and there are no statistically significant differences between the means of the total score for the psychological Hardiness scale in the study sample due to the school stage variable. The study ended with recommendations that emphasize the provision of formal and informal nurturing and supportive environments to enhance the psychological Hardiness of adolescent girls affected by the pandemic.
Keywords: Social Support; Psychological Hardiness; Adolescence; Corona Pandemic